ANALYSIS OF THE UTILIZATION OF THE ADMINISTRATIVE EXEMPTION OF HOTEL TAX, RESTAURANT TAX, AND ENTERTAINMENT TAX IN ACCORDANCE WITH MAYOR REGULATION NO. 42 YEAR 2021 BITUNG CITY - Madeleine Monica Roslin Ole; Jenny Morasa; Sonny Pangerapan (Universitas Sam Ratulangi, 2022)
Tax sanctions are divided into two types, namely administrative sanctions and criminal sanctions. The taxpayer's duty to pay hotel, restaurant, and entertainment taxes in the pandemic era is felt to burden the community, especially those in the city of Bitung. Therefore, the local government issued a policy through Mayor Regulation No. 42 in 2021 in terms of granting exemption from administrative sanctions. The purpose of this study was to determine the use of the exemption from administrative sanctions for Hotel Tax, Restaurant Tax, and Entertainment Tax in Bitung City in accordance with Mayor Regulation No. 42 in 2021. The analytical method used in this study is a qualitative descriptive analysis. The results of this study indicate that there are 22 Restaurant Taxpayers, 5 Hotel Taxpayers, and 4 Entertainment Taxpayers who take advantage of the exemption of sanctions. For those who do not take advantage, there are 15 Restaurant Taxpayers and 4 Hotel Taxpayers with constraints of lack of information and economic difficulties. The method of paying taxes during the exemption period is still the same as the normal payment, but the Taxpayer is no longer subject to administrative sanctions.